Frequency of endometriotic lesions in peritoneum samples from asymptomatic fertile women and correlation with CA125 values - Barbosa, Caio Parente [UNIFESP] (2009)
CONTEXT AND OBJECTIVE: Serological testing for CA125 has been widely used to detect endometriosis and to monitor its progression. However, controversy still exists regarding the usefulness of the plasma CA125 assay for diagnosing endometriosis. Furthermore, some authors have described superficial endometriosis as a cyclical and normal phenomenon in women's lives, and have indicated that development and progression of this disease would only occur in some women as a result of immunological changes. This study aimed to determine the frequency of endometriosis and the correlation between serum CA125 levels and the presence of endometriotic lesions in the peritoneum of asymptomatic fertile patients. DESIGN AND SETTING: Cross-sectional study at the Family Planning outpatient clinic of Faculdade de Medicina do ABC. METHODS: Eighty asymptomatic fertile patients who underwent tubal sterilization surgery were studied. Blood and peritoneum samples were collected. CA125 levels were measured from blood samples, and peritoneum biopsies were studied using histopathological tests. RESULTS: Histopathological evaluation of the peritoneum revealed that 16.25% of the patients had minimal or mild endometriosis. There was no statistically significant difference in CA125 levels between patients with and without endometriosis. CONCLUSION: The presence of endometriotic lesions in the peritoneum of fertile patients supports the hypothesis that incidental findings of minimal or mild endometriosis may not be of clinical significance, and that the progression of the disease probably occurs as a result of immunological and genetic abnormalities. Serum CA125 levels did not show any diagnostic significance with regard to detecting the disease.